Smartphone-based prenatal attachment education application design improving maternal and fetal attachment to high-risk pregnant mothers at Putri Ayu Health Center Jambi City - Herinawati Herinawati; Yuli Suryati; Osvinarti Osvinarti; Melyana Nurul Widyawati; Iksaruddin Iksaruddin (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2022)
Background: The prevalence of high-risk pregnancies in the world is still relatively high. Approximately 10-30% of mothers who undergo routine antenatal care are diagnosed with high-risk pregnancies and of these, 70-80% experience perinatal mortality and morbidity. The psychological impact of high-risk pregnancy is anxiety, stress, and the mother experiencing a crisis that can affect the relationship between the mother and the fetus. This condition can also continue in the relationship between mother and baby after birth. Therefore, it is necessary to make efforts to increase the attachment of mother and fetus, one of which can be done by providing education. The purpose of this study was to determine the effect of Android-based Prenatal Attachment Education Applications on Maternal and Fetal Attachment in High-Risk Pregnant Women. Methods: This type of research is quantitative with a quasi-experimental design study that uses a one group pretest - posttest design without control group. The intervention provided was in the form of prenatal attachment education packaged in an application via mobile phones. The research sample was 40 pregnant women at Putri Ayu Public Health Center, Jambi City. The inclusion criteria in this study were pregnant women who could read and write. Exclusion criteria were respondents who were not willing to participate in the study. Results: Based on the results of the above analysis, it can be seen that Sig is 0.000 < 0.001, which means that H0 is rejected and Ha is accepted. In other words, there is a significant relationship between the application of prenatal attachment education with maternal and fetal attachment. Conclusion: maternal and fetal attachment can be improved with prenatal attachment education applications, for that it is expected that the puskesmas implement prenatal attachment education applications using mobile phones so that they can increase maternal and fetal attachment.